Pattern Interception of Coffee Plants in The Laboratory Scale Using the Rainfall Simulator with the Quite Heavy – Heavy Rain Intensity - Naimah, Lilik Imron; Wirosoedarmo, Ruslan; Rahadi, J. Bambang (Jurnal Teknologi Pertanian, 2008)
Hydrology is the science of learning and the provision of movement under and upper water on the earth surface.  There are many events in the hydrological cycles such as infiltration, percolation, run off, evaporation, transpiration, and interception. The interception is the event where rainfall felt on the vegetation of land surface is retained for a moment before evaporation into the atmosphere.  Interception is influenced some factors which are plant species, plant age, canopy shape, canopy with, leaf position. Therefore the existence of the canopy can inhibit rainfall to fall   on the land surface.Research on the interception is still limited. Generally, the value of interception is small, but it highly influences the occurrence of erosion.  This research was conducted to determine the magnitude of interception by simulation model.  The modeling used rainfall simulator as a tool. The objectives of this research were to know the relationship between the amount of rainfall and interception on coffee plants and to know the interception feature pattern of coffee plants using rainfall simulator.  The research used 3 heights of the plants, 3 rain conditions, and 5 densities of the plants (50%, 60%, 70%, 80% and 90%). The data obtained was analyzed by statistical analysis.  It was aimed to determine the relationship between variables assessed. Interception pattern of coffee plants based on density increased as the plant density increased.  The plant density of 90% had the highest interception value for each plant height. The magnitude of interception of coffee plants based on rainfall conditions which were quite heavy (intensity of 66,294 mm/hour), heavy-1 (intensity of 93,116 mm/hour) and heavy-2 (intensity of 133,35 mm/hour), showed the interception increased as the intensity increased.  The interception and precipitation showed positive correlation and logarithmic relationship.Keywords: hydrology, interception, rainfall simulator, simulation